MENINGKATKAN KREATIFITAS MENGGAMBAR ANAK SEKOLAH DASAR - Rahman, Muhammad Arif; Faiz, Akhmad Naufal; Primadoni, Ade Bagus; Akhmad, Yanuar; Faida, Mar’atul (Nindikayla Institute, 2022)
Based on observations at Josari 01 Elementary School in Tersono District, children's creativity in drawing is still low, because so far, whenever there is a drawing learning activity, children are reluctant to be invited to do activities related to children's fine motor skills. But prefer to choose to play with gadgets and friends than doing activities that are done individually. Therefore this community service aims to improve the creative ability to draw elementary school children in Tersono District, Batang Regency and its surroundings which we focus on children's drawing creativity. The method used is through workshops and drawing assistance for elementary school students in Tersono District, Batang Regency and its surroundings. This community service activity is divided into three sessions, namely the first session provides knowledge about the history of drawing including understanding, history, and types of drawings. The second session was a drawing competition session carried out by all participants. Furthermore, the last session was an assessment session to determine 1st, 2nd and 3rd place winners. The community service program that had been carried out by the STKIP Muhammadiyah Batang Elementary School Teacher Education Study Program had been carried out well and received positive impressions from all participants who took part.